Rethinking Citizenship Education : a curriculum for participatory democracy. - McCowan, Tristan (Continuum studies in educational research., 2009)
Rethinking Citizenship Education presents a fundamental reassessment of the field. Drawing on empirical research, the book argues that attempting to transmit preconceived notions of citizenship through schools is both unviable and undesirable. The notion of ''curricular transposition'' is introduced, a framework for understanding the changes undergone in the passage between the ideals of citizenship, the curricular programmes designed to achieve them, their implementation in practice and the effects on students. The ''leaps'' between these different stages make the project of forming students.